PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KOMPETENSI PENGETAHUAN DAN KETRAMPILAN BERPIKIR KRITIS SISWA MADRASAH ALIYAH BPD IHA TENTANG KONFLIK - Hallatu, Yosepus; Prasetyo, Ketut; Haidar, Ali (Universitas Negeri Semarang, 2017)
This study aimed is to determine the effect of problem based learning model of the competence of knowledge and critical thinking skills of students about the conflict between the villages. This study uses experimental research design. The techniques of pretest-posttest randomized control design is used in this study. The population was the whole of the class XI at Madrasah Aliyah BPD (board of villages organizer ) Iha in Maluku Province which consists of three classes. While the sample consisted of two classes, namely XI 2 as an experimental class that implements the model problem based learning and XI 3 as the control class that implements direct instructional model. The t-test is used to analize the data . The results showed that the descriptive analysis model of problem based learning effect to enhance the competence of knowledge and critical thinking skills of students based on several things, namely: (1) the students activity is categorized actif, (2) completeness of the learning outcomes achieved. This is indicated by sig 0,000 ≤ 0.05 and the t calculated (5.637) ≥ t table (1.688). This means that there are differences in the average post-test students on the model of problem based learning is better than direct learning model in terms of improving the knowledge and competence of critical thinking skills.